1999
DOI: 10.1523/jneurosci.19-19-08542.1999
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Explanation of the Cornsweet Effect

Abstract: A long-standing puzzle in vision is the assignment of illusory brightness values to visual territories based on the characteristics of their edges (the Craik-O'Brien-Cornsweet effect). Here we show that the perception of the equiluminant territories flanking the Cornsweet edge varies according to whether these regions are more likely to be similarly illuminated surfaces having the same material properties or unequally illuminated surfaces with different properties. Thus, if the likelihood is increased that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
78
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(85 citation statements)
references
References 35 publications
5
78
0
1
Order By: Relevance
“…Although we cannot rule out the possibility that cortical interactions of this sort play some part in the distorted perception of angles, the results we report here support a more general explanation that accords with the way a number of other puzzling perceptions have recently been rationalized (17)(18)(19)(20)(21)(22). Visual percepts-whether of luminance, spectral returns, or, in the present case, oriented lines-can be understood as the consequence of an entirely empirical strategy in which the percept experienced is an association determined by the relative frequency of occurrence of the possible sources of an ambiguous retinal stimulus, this information being gleaned from the success or failure of the behavioral responses that have been made to the same or similar stimuli in the past.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…Although we cannot rule out the possibility that cortical interactions of this sort play some part in the distorted perception of angles, the results we report here support a more general explanation that accords with the way a number of other puzzling perceptions have recently been rationalized (17)(18)(19)(20)(21)(22). Visual percepts-whether of luminance, spectral returns, or, in the present case, oriented lines-can be understood as the consequence of an entirely empirical strategy in which the percept experienced is an association determined by the relative frequency of occurrence of the possible sources of an ambiguous retinal stimulus, this information being gleaned from the success or failure of the behavioral responses that have been made to the same or similar stimuli in the past.…”
Section: Discussionsupporting
confidence: 57%
“…represent the empirical significance of the proximal stimulus, determined by the accumulated instruction of past experience (17)(18)(19)(20)(21)(22). Narrowly put, the advantage of this strategy is that similar or even identical proximal stimuli will appear different if their sources are likely to be different, as a result of past experience.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the difference between experiments 1 and 2 raises the possibility that attention modulation plays a role in surface formation. Second, it has been reported that brightness, as well as color perception, can be drastically different depending on the context (13,14). Thus, we conclude that surface representation formation cannot be explained by a single mechanism in one visual area in solely top-down or bottom-up processing.…”
Section: Discussionmentioning
confidence: 57%
“…One reason for this controversy may be the tacit assumption that surface representation is accomplished by single processing rather than multiple processing. Surface representation could be a result of many different aspects of processing (13)(14)(15). It comprises various subcomponents such as contours, brightness, color, depth, and motion, each of which could work differently or interact with each other to engender perception of a surface in the brain (16)(17)(18)(19).…”
mentioning
confidence: 99%